Silver complexes with sulfathiazole and sulfamethoxazole: Synthesis, spectroscopic characterization, crystal structure and antibacterial assays. (8th January 2015) - Bormio Nunes, Julia Helena; de Paiva, Raphael Enoque Ferraz; Cuin, Alexandre; Lustri, Wilton Rogério; Corbi, Pedro Paulo
Abstract : Graphical abstract: Structure of the silver complex with sulfathiazole obtained by powder X-ray crystallographic studies. Abstract: The present work describes the synthesis and spectroscopic characterization of two silver(I) complexes with the sulfonamides sulfathiazole (AgC9 H8 N3 O2 S2, Ag-SFT) and sulfamethoxazole (AgC10 H10 N3 O3 S, Ag-SFM). Elemental analyses indicate a 1:1 metal/ligand composition for both complexes. Spectroscopic techniques such as 1 H, 15 N NMR and IR evidence the coordination of both ligands to silver through the nitrogen atom of the sulfonamide group, and also indicate the participation of the 5-membered N-heterocyclic ring in the coordination. The Ag-SFT crystal structure was solved by X-ray powder diffraction and indicates the formation of a dimeric structure with silver bridging between two ligand molecules. Biological studies showed the antibacterial activity of Ag-SFT and Ag-SFM complexes against Gram-positive and Gram-negative bacterial strains, with MIC values ranging from 3.45 to 6.90 mmol L −1 for the sulfathiazole complex and 1.74 to 13.9 mmol L −1 for the sulfamethoxazole complex. The complexes have shown to be more active against Gram-negative bacterial strains.